Analysis of Romania’s external debt and the implications for foreign relations during 2000-2013 - Geamanu, Marinela; Popescu, Barbu Bogdan (Annals of Spiru Haret University. Economic Series, 2016)
In this paper, we performed an analysis of the time series of the indicator by effect – GD P with the indicator by effort – external debt, great relevance macroeconomic indicators. This study is based on analyses and comparative statistical correlations about external debt, research analysis will be based on secondary data, based on information provided by the Romanian Statistical Yearbook published by the National Institute of Statistics and other publications of public institutions Romania. The originality of this work lies in combining research methods and statistical techniques used for time series that are total research for characterizing macroeconomic variables such as economic growth and external debt.